Maturity timing and performance in a youth national basketball team: Do early-maturing players dominate?. Issue 3 (June 2021) - Arede, Jorge; Fernandes, John; Moran, Jason; Norris, Jonty; Leite, Nuno
The aims of this study were to examine the influence of maturity timing on functional skills and game-related statistics amongst under-16 (U16) national team basketball players, and analyse which of these parameters were related to onward selection to the under-18 (U18) national team. Thirty-six U16 basketball players underwent anthropometric and overhead squat assessments during a national team training camp. Also, maturity offset (MO) was computed alongside game-related statistics during the U16 National Championship and U16 European Championship competitions. For the statistical analysis of all parameters, subjects were identified according to their maturity timing (early vs average). Sitting height, height, body mass, points scored and assists during U16 National Championship discriminated between early- and average-maturing players. Early-maturing players played significantly fewer minutes during the European Championship compared with the National Championship whilst average-maturing players scored significantly more points and performed more assists during the National Championship. Minutes played during the European Championship, and points scored during National and European Championships discriminated 'selected' from 'non-selected' players for the U18 National Team. These results encourage coaches to acknowledge the value in allowing later-maturing players the time to develop with a view to realising their full potential.